Water and nitrogen use efficiency in SRI through AWD and LCC - SINGH, A K; CHAKRABORTI, MANDIRA (The Indian Journal of Agricultural Sciences, 2019)
A farmer-participatory field experiment was conducted in Tripura, NE India to find out the relative efficiency of integrated use of leaf colour chart (LCC), alternate wetting and drying (AWD) and system of rice intensification (SRI). The rice was grown during the rabi (2012–13 to 2014–15) under two crop stand establishment methods of, system of rice intensification (SRI), and Conventional Rice Culture (CRC). The results of AWD for the water management in rice farming under SRI revealed that ~30% of irrigation water can be saved over conventional flooding method. The use of LCC was helpful to ascertain the amount of N fertilizer and its time of application for maintaining an optimal leaf N content and achieving higher rice yield. Agronomic efficiency (AEN) was significantly higher (73%), which resulted in more than 47% higher yield and N uptake over recommended N application. The adoption of AWD and N application with LCC (< 4) timing were the optimum and best methods of water and N management for transplanted rice under SRI.